Allergies in Sahelian Africa - (:unkn) unknown (My University, 2018)
Within the next thirty years, the Sahelian countries will have more than 200 million inhabitants, nearly 50 million of whom will be living in the urban areas of their nations’ capitals. In these cities, particulate matter produced by vehicles and cooking combines with the fine dust brought from the Sahara by the Harmattan wind between November and May, causing increased mortality from infectious and cardiovascular diseases, as well as a rise in symptoms of respiratory allergy. The wide variety of pollens from tropical grasses and their genetic distance from European or North American grass species render the available diagnostic tests practically useless. Conversely, sensitization to mites can be explored using standard allergenic extracts. Helminth infestation and insect bites lead to the production of IgE directed against carbohydrates epitopes. These anti-carbohydrate IgEs (directed against MMXF3, MUXF3 and α-galactose) produce false positive results in specific IgE assays in which glycosylated protein extracts are used. This false positivity is present for legumes and mammalian dander, even in the absence of allergic symptoms in the patients being tested. The use of non-glycosylated allergenic components could facilitate the identification of truly sensitized and allergic subjects. However, the contribution of recombinant allergens to diagnosis in African patients requires further confirmation by means of clinical and laboratory studies.
Keywords: African Research